SISTEM PENGINGAT PADA GUDANG PT. ALFA BEAUTY COSMETICA MENGGUNAKAN SMS GATEWAY - Warisman, Arey Nur; Salamah, Umniy; Jumaryadi, Yuwan (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
The development of technology is very important for humans, especially in the field of storage of goods that become a useful and important thing in the world of warehousing. In this study the authors take a case study at PT. Alfa Beauty CosmeticaÂ who still uses warehouse reports manually. This study aims to facilitate the work of employees of PT. Alfa Beauty Cosmetica. Employees can store in-app items consisting of goods unique code, item name, recording location of goods and recording transactions of goods. Message reminder simulation is if stock will run out using web based Gateway SMS. With stock reminder messages, employees are quicker at updating inventory. This application is expected to accelerate employee work.